2017
DOI: 10.1016/j.cub.2017.07.052
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila PAF1 Modulates PIWI/piRNA Silencing Capacity

Abstract: SUMMARY To test the directness of factors in initiating PIWI-directed gene silencing, we employed a Piwi-interacting RNA (piRNA)-targeted reporter assay in Drosophila OSS cells [1]. This assay confirmed direct silencing roles for piRNA biogenesis factors and PIWI-associated factors [2–12], but suggested that chromatin-modifying proteins may act downstream of the initial silencing event. Our data also revealed that RNA Polymerase II associated proteins like PAF1 and RTF1 antagonizes PIWI-directed silencing. PAF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 48 publications
4
18
0
Order By: Relevance
“…In addition to Eggless‐KD, H1‐KD and HP1‐KD also had no impact on the silencing by Piwi–piRNA and λN‐Nxf2 in the reporter system based on plasmids (Figs EV3F and EV4G–J). While this result is consistent with a report of a study using a plasmid‐based reporter assay to detect Piwi‐directed silencing in Drosophila ovary somatic sheet cells (Clark et al , ), it is at odds with previous reports demonstrating that the methyltransferase Eggless is required for Panx‐mediated silencing using the tethering system in the Drosophila ovary (Sienski et al , ; Yu et al , ). These conflicting results are probably due to the different expression systems of λN fusion proteins.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In addition to Eggless‐KD, H1‐KD and HP1‐KD also had no impact on the silencing by Piwi–piRNA and λN‐Nxf2 in the reporter system based on plasmids (Figs EV3F and EV4G–J). While this result is consistent with a report of a study using a plasmid‐based reporter assay to detect Piwi‐directed silencing in Drosophila ovary somatic sheet cells (Clark et al , ), it is at odds with previous reports demonstrating that the methyltransferase Eggless is required for Panx‐mediated silencing using the tethering system in the Drosophila ovary (Sienski et al , ; Yu et al , ). These conflicting results are probably due to the different expression systems of λN fusion proteins.…”
Section: Resultssupporting
confidence: 91%
“…Recently, it was reported that Pol II‐associated proteins, PAF1 and RTF1, antagonize Piwi‐directed silencing (Clark et al , ), which are factors involved in the modulation of promoter release, elongation, and termination of Pol II (Chen et al , ; Van Oss et al , ; Vos et al , ). The Panx–Nxf2–P15 complex might interfere with Pol II via the PAF1 complex, considering that fission yeast PAF1 represses AGO1/siRNA‐directed silencing (Kowalik et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to Eggless-KD, H1-KD and HP1-KD also had no impact on the silencing by Piwi–piRNA and λN-Nxf2 in the reporter system based on plasmids (Figures S3F and S4G-J). While this result is consistent with a report of a study using a plasmid-based reporter assay to detect Piwi-directed silencing in Drosophila ovary somatic sheet cells (Clark et al, 2017), it is at odds with previous reports demonstrating that the methyltransferase Eggless is required for Panx-mediated silencing using the tethering system in the Drosophila ovary (Sienski et al, 2015; Yu et al, 2015). These conflicting results are probably due to the different expression systems of λN fusion proteins.…”
Section: Resultssupporting
confidence: 91%
“…Small RNA libraries were sequenced as 75bp single end reads on the NextSeq550. Adapters for the small RNA libraries were removed with CutAdapt and then mapped to the Drosophila transposon consensus sequences from RepBase and Flybase using Bowtie v1 with 1 mismatch and R plotting scripts as applied in our previous published studies on Drosophila piRNAs (Clark et al, 2017; Sytnikova et al, 2014).…”
Section: Methodsmentioning
confidence: 99%